Show that evaluate tan 48° tan 23° tan 42° tan 67° = 1

Asked by Abhisek | 1 year ago |  61

##### Solution :-

tan 48° tan 23° tan 42° tan 67°

Simplify the given problem by converting some of the tan functions to the cot functions

We know that, tan 48° = tan (90° – 42°) = cot 42°

tan 23° = tan (90° – 67°) = cot 67°

= tan (90° – 42°) tan (90° – 67°) tan 42° tan 67°

Substitute the values

= cot 42° cot 67° tan 42° tan 67°

= (cot 42° tan 42°) (cot 67° tan 67°) = 1×1 = 1

Answered by Pragya Singh | 1 year ago

### Related Questions

#### Prove the sinθ sin (90° – θ) – cos θ cos (90° – θ) = 0

Prove the sinθ sin (90° – θ) – cos θ cos (90° – θ) = 0

#### Prove that sin 48° sec 48° + cos 48° cosec 42° = 2

Prove that sin 48° sec 48° + cos 48° cosec 42° = 2

#### Prove that tan 20° tan 35° tan 45° tan 55° tan 70° = 1

Prove that tan 20° tan 35° tan 45° tan 55° tan 70° = 1

#### Evaluate the 2sin 3x = \sqrt{3}

Evaluate the $$2sin 3x = \sqrt{3}$$

#### Evalute the following: sin 20°/ cos 70°

Evalute the following:

(i) $$\dfrac{sin 20°}{ cos 70°}$$

(ii) $$\dfrac{ cos 19°}{ sin 71°}$$

(iii) $$\dfrac{sin 21°}{ cos 69°}$$

(iv) $$\dfrac{tan 10°}{ cot 80°}$$

(v) $$\dfrac{sec 11°}{ cosec 79°}$$